2006
DOI: 10.1073/pnas.0603786103
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of Nck adaptors for actin dynamics and cell migration stimulated by platelet-derived growth factor B

Abstract: Crk-associated substrate ͉ actin cytoskeleton ͉ SH2 domain ͉ SH3 domain ͉ tyrosine phosphorylation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
81
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(89 citation statements)
references
References 30 publications
8
81
0
Order By: Relevance
“…Dorsal ruffles are thought to constitute a non-clathrin pathway for the sequestration and internalization of tyrosine kinase receptors (26). A similar correlation between Nck and the formation of dorsal ruffles has been observed in another study (27). Interestingly, dorsal ruffles are also missing in cells lacking N-WASP or WAVE1 (28,29).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Dorsal ruffles are thought to constitute a non-clathrin pathway for the sequestration and internalization of tyrosine kinase receptors (26). A similar correlation between Nck and the formation of dorsal ruffles has been observed in another study (27). Interestingly, dorsal ruffles are also missing in cells lacking N-WASP or WAVE1 (28,29).…”
Section: Discussionsupporting
confidence: 56%
“…Observations of PI3K-independent PDGF-induced chemotaxis also suggest that Nck is involved this process (33). Nck is also likely to collaborate with the Crk-associated substrate (p130 Cas ) during PDGF-BB-induced cell migration (27). We noticed that the PDGF-BB-induced chemotactic capacity of the KO cells was reduced to half that of the maximum capacity seen in wild-type cells.…”
Section: Discussionmentioning
confidence: 60%
“…Mouse embryonic fibroblast (MEF) cell lines generated from Nck1+/ +;Nck2+/+ (Nck1+/Nck2+), Nck12/2;Nck2+/+ (Nck12/ Nck2+), Nck1+/+;Nck22/2 (Nck1+/Nck22) and Nck12/ 2;Nck22/2 (Nck12/Nck22) embryos were kindly provided by Tony Pawson (Samuel Lunenfeld Research Institute, Toronto, ON, Canada) and have been described previously (Bladt et al, 2003;Gruenheid et al, 2001). Nck12/Nck22 cells complemented with wild-type human Nck1 or a dominant-negative version of Nck1 with inactivating mutations in all three SH3 domains (Kall) were kindly provided by Tony Pawson (Samuel Lunenfeld Research Institute) and have been described previously (Rivera et al, 2006;Tanaka et al, 1995). Cell lines were grown in Dulbecco's minimal Eagle's medium (DMEM) supplemented with 10 % (v/v) fetal calf serum (DMEM/ FCS) at 37 uC in a humidified atmosphere with 5 % CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the authors of this study concluded that Nck␣ and Nck␤ are functionally redundant during mouse development. However, an increasing number of studies have also provided evidence that Nck␣ and Nck␤ have rather nonoverlapping functions in various type of cells (5,6,14,19,21,25). So far, no Nck␣-or Nck␤-specific downstream target proteins have been identified, and it has obviously become critical to further understand the underlying mechanisms.…”
mentioning
confidence: 99%